Immunogenetic heterogeneity in a widespread ungulate: the European roe deer (Capreolus capreolus). Issue 15 (17th July 2015) - Quéméré, Erwan; Galan, Maxime; Cosson, Jean‐François; Klein, François; Aulagnier, Stéphane; Gilot‐Fromont, Emmanuelle; Merlet, Joël; Bonhomme, Maxime; Hewison, A. J. Mark; Charbonnel, Nathalie
Abstract Understanding how immune genetic variation is shaped by selective and neutral processes in wild populations is of prime importance in both evolutionary biology and epidemiology. The European roe deer (Capreolus capreolus) has considerably expanded its distribution range these last decades, notably by colonizing agricultural landscapes. This range shift is likely to have led to bottlenecks and increased roe deer exposure to a new range of pathogens that until recently predominantly infected humans and domestic fauna. We therefore investigated the historical and contemporary forces that have shaped variability in a panel of genes involved in innate and acquired immunity in roe deer, including Mhc‐Drb and genes encoding cytokines or toll‐like receptors (TLRs). Together, our results suggest that genetic drift is the main contemporary evolutionary force shaping immunogenetic variation within populations. However, in contrast to the classical view, we found that some innate immune genes involved in micropathogen recognition (e.g. Tlrs) continue to evolve dynamically in roe deer in response to pathogen‐mediated positive selection. Most studied Tlrs (Tlr2, Tlr4 and Tlr5) had similarly high levels of amino acid diversity in the three studied populations including one recently established in southwestern France that showed a clear signature of genetic bottleneck. Tlr2 implicated in the recognition of Gram‐positive bacteria in domestic ungulates, showed strong evidence of balancing selection. The high immunogenetic variation revealed here implies that roe deer are able to cope with a wide spectrum of pathogens and to respond rapidly to emerging infectious diseases.